2022
DOI: 10.3390/jof8050499
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Efficacy of Amphotericin B against Four Candida auris Clades

Abstract: Candida auris is a multidrug-resistant fungus against which in some clinical situations amphotericin B (AMB) remains the alternative or first line drug. We compared daily 1 mg/kg of AMB efficacy in a neutropenic murine bloodstream infection model against 10 isolates representing four C. auris clades (South Asian n = 2; East Asian n = 2; South African n = 2; South American n = 4; two of which were of environmental origin). Five days of AMB treatment significantly increased the survival rates in mice infected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The isolate with the aggregative phenotype showed higher in vitro MIC values compared to the non-aggregative isolates both in monotherapy and in combination assays. Interestingly, it has been suggested that the formation of aggregates may be a survival strategy of C. auris ( 20 ), which has also been observed in vivo ( 59 ). Based on our findings, when MIC values of antifungal susceptibility testing are high in monotherapy for a C. auris isolate, combination therapy has been shown to be a good alternative to reduce drug concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The isolate with the aggregative phenotype showed higher in vitro MIC values compared to the non-aggregative isolates both in monotherapy and in combination assays. Interestingly, it has been suggested that the formation of aggregates may be a survival strategy of C. auris ( 20 ), which has also been observed in vivo ( 59 ). Based on our findings, when MIC values of antifungal susceptibility testing are high in monotherapy for a C. auris isolate, combination therapy has been shown to be a good alternative to reduce drug concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro model using an artificial human axillary sweat medium and ex vivo porcine skin as a substrate, C. auris was able to produce dense, multilayered accumulation [98]. Interestingly, C. auris exhibited a fungal burden 10-fold greater than that of C. albicans in the artificial sweat medium but not RPMI-MOPS, along with an apparent persistence of C. auris in concentrated [24,25,28,[77][78][79][80][81][82][83][84] directly comparing virulence between isolates of different clades (A) or body site origins (B) in animal infection models. For each study, the virulence of each isolate was ranked by mortality and median survival.…”
Section: Host Colonizationmentioning
confidence: 98%
“…For experimental virulence models, 11 reports of invertebrate or murine infection models [24,25,28,[77][78][79][80][81][82][83][84] were identified that met the acceptance criteria of having (1) Multiple isolates with clade or body site origin indicated; (2) Identical infection protocol between isolates; and (3) Survival data available. Because of the small number of studies available, an acceptance criteria including any study that compared more than 1 isolate from different groups was established, with the anticipated limitation that studies with small sample sizes might exhibit greater variation from a true effect.…”
Section: Topical Focusmentioning
confidence: 99%
See 2 more Smart Citations